Genome sequence and analysis of Lactobacillus helveticus - Cremonesi, Paola; Chessa, Stefania; Castiglioni, Bianca (Frontiers in Microbiology, 2013)
The microbiological characterization of lactobacilli is historically well developed, but the genomic analysis is recent. Because of the widespread use of L. helveticus in cheese technology, information concerning the heterogeneity in this species is accumulating rapidly. Recently, the genome of five L. helveticus strains was sequenced to completion and compared with other genomically characterized lactobacilli. The genomic analysis of the first sequenced strain, L. helveticus DPC 4571, isolated from cheese and selected for its characteristics of rapid lysis and high proteolytic activity, has revealed a plethora of genes with industrial potential including those responsible for key metabolic functions such as proteolysis, lipolysis, and cell lysis. These genes and their derived enzymes can facilitate the production of cheese and cheese derivatives with potential for use as ingredients in consumer foods. In addition, L. helveticus has the potential to produce peptides with a biological function, such as angiotensin converting enzyme (ACE) inhibitory activity, in fermented dairy products, demonstrating the therapeutic value of this species. A most intriguing feature of the genome of L. helveticus is the remarkable similarity in gene content with many intestinal lactobacilli. Comparative genomics has allowed the identification of key gene sets that facilitate a variety of lifestyles including adaptation to food matrices or the gastrointestinal tract. As genome sequence and functional genomic information continues to explode, key features of the genomes of L. helveticus strains continue to be discovered, answering many questions but also raising many new ones.